Students’ Science Literacy on Discussion-Based Contextual Approaches of Human Reproductive System Learning - Yeni Mulyaningsih; Chaerul Rochman; Adam Malik; Tri Wahyu Agustina; Yulia Sukmawardani; Nur Hamidah; Nurul Annisa (Jurnal Pendidikan Sains, 2024)
The aim of this study was to enhance students’ science literacy through a discussion-based contextual approach in the learning of the human reproductive system. This quantitative research employed an experimental method with a quasi-experimental posttest-only design. The study involved 60 students, with 30 students each in class XI MIPA 4 serving as the experimental group and class XI MIPA 5 serving as the control group. The control group received instruction through a conceptual approach-based lecture method, whereas the experimental group engaged in learning through a contextual approach-based discussion method. The research instrument comprised 10 open-ended science literacy questions pertaining to the human reproductive system. The data were analyzed using an independent t-test with SPSS version 26. The results indicated that the data were both normally distributed and homogeneous. Furthermore, a significant difference was observed between the control and experimental groups, with a t-count value of 4.118, which is greater than the t-table value of 1.671. In conclusion, the study demonstrates that the human reproductive system can be effectively taught through contextual experiences relevant to students’ lives, thereby enhancing their science literacy skills.DOI: 10.17977/jps.v12i22024p071